1977
DOI: 10.1159/000240984
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Placental Blood Flow in the Pig and Its Relation to Placental and Fetal Weight

Abstract: In 12 pregnant sows (Sus scrofa domestica), containing 144 live fetuses, placental blood flow was measured by the indicator fractionation technique using radioactive microspheres. In 8 of these litters, which contained 96 live fetuses, placental blood flow was obtained in absolute units. Significant positive correlations were observed between placental blood flow and placental weight, between placental blood flow and fetal weight, and between placental weight and fetal weight. It is clear that the runt, by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
3

Year Published

1981
1981
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 6 publications
(7 reference statements)
3
34
0
3
Order By: Relevance
“…The results support the idea that fetal growth is largely dependent on the availability of nutrients and oxygen determined by the rate of placental blood flow (3,12). The smaller placental size, which in the small fetuses is proportional to the fetal growth retardation, is probably also determined by the reduced placental blood flow.…”
Section: Discussionsupporting
confidence: 82%
“…The results support the idea that fetal growth is largely dependent on the availability of nutrients and oxygen determined by the rate of placental blood flow (3,12). The smaller placental size, which in the small fetuses is proportional to the fetal growth retardation, is probably also determined by the reduced placental blood flow.…”
Section: Discussionsupporting
confidence: 82%
“…Conditions associated with reduced rate of fetal growth (e.g. maternal genotype, increased numbers of fetuses, maternal nutrient deprivation, environmental heat stress) are also associated with reduced rates of placental blood flow and fetal oxygen and nutrient uptakes (Wootton et al, 1977;Morriss et al, 1980;Reynolds et al, 1985a, b;. Reduced rate of fetal growth can lead to decreased birth weight, which has a major impact on neonatal survival and growth (Record et al, 1952;Anderson et al, 1978;Fahmy et al, 1978;Huffman et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that placentas supplying the smallest fetus in the uterus are disproportionally lighter than those supplying average-sized fetuses in the same litter (Ashworth et al 2001). These data, combined with the positive relationship between placental blood flow and fetal weight in the pig (Wootton et al 1977), imply that there is a generalised reduction in the ability of placentas supplying small fetuses to deliver nutrients. In addition, there is increasing evidence in a variety of species, including rat, guinea pig, sheep and human, of an association between placental amino acid transport and fetal growth (reviewed in Sibley et al 1997).…”
Section: Introductionmentioning
confidence: 90%